1975
DOI: 10.1021/bi00690a028
|View full text |Cite
|
Sign up to set email alerts
|

Sites of biological methylation of proteins in cultured chick muscle cells

Abstract: The methylation of myosin and other proteins has been studied using primary cultures of 12-day-old embryonic chick leg muscle. The methyl group of [Me-3H] methionine is incorporated into basic amino acid residues with the formation of Nepsilon-monomethyllysine, Nepsilon-dimethyllysine, Nepsilon-trimethyllysine, 3-methylhistidine, NG-monomethylarginine, and NG-dimethylarginine which are isolated from acid hydrolysates of purified myosin, and of proteins from polysomes and from the cytosol of the cultured muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

1978
1978
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 65 publications
1
14
0
1
Order By: Relevance
“…The turnover of 3-methylhistidine in skeletal muscle protein was 35% of the overall rate of mixed muscle protein synthesis irrespective of whether it was measured 1 h or 4-5 h after injection of tracer [23,24]. This confirms the results of others, who have shown no differences between rates of methylation and overall protein synthesis [26,27].…”
Section: Lhmover Of Skeletal Muscle 3-methylhistidinesupporting
confidence: 83%
“…The turnover of 3-methylhistidine in skeletal muscle protein was 35% of the overall rate of mixed muscle protein synthesis irrespective of whether it was measured 1 h or 4-5 h after injection of tracer [23,24]. This confirms the results of others, who have shown no differences between rates of methylation and overall protein synthesis [26,27].…”
Section: Lhmover Of Skeletal Muscle 3-methylhistidinesupporting
confidence: 83%
“…In mammals, certain proteins contain N'trimethyl-lysine (TML) residues [16]. N-methylation of these lysine residues occurs as a post-translational event in proteins such as calmodulin, myosin, actin, cytochrome c and histones [17,18]. This reaction is catalysed by specific methyltransferases, which use S-adenosylmethionine as a methyl donor [16].…”
Section: Figure 2 the Carnitine Biosynthesis Pathwaymentioning
confidence: 99%
“…This process of basic amino acid methylation became well documented [17] and it was recognised that arginine methylation occurred shortly after protein synthesis. Incorporation of radiolabelled methyl groups onto the arginine residues of myelin basic protein revealed that once methylated the reaction appeared to be irreversible and the arginine-methylated protein took weeks to degrade [18,19].…”
Section: Adma Synthesismentioning
confidence: 97%